2015
DOI: 10.3109/00016489.2015.1079926
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course of persistent geotropic direction-changing positional nystagmus with neutral position—Light cupula

Abstract: The nystagmus had resolved within a week in 70% and within 30 days in 89% of the patients. The recurrence rate was 33%. The subjects did not have a history of alcohol intake, head trauma, or vestibular neuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…[ 16 18 ] Zucca et al [ 16 ] reported that the spontaneous dissolution of otoconia usually took 2 to 6 weeks, while the positional nystagmus caused by “light cupula” could last longer than 6 months. [ 17 ] Therefore, the theory of spontaneous dissolution of otoconia or “heavy cupula” still does not explain the early spontaneous remission of apo-DCPN in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 18 ] Zucca et al [ 16 ] reported that the spontaneous dissolution of otoconia usually took 2 to 6 weeks, while the positional nystagmus caused by “light cupula” could last longer than 6 months. [ 17 ] Therefore, the theory of spontaneous dissolution of otoconia or “heavy cupula” still does not explain the early spontaneous remission of apo-DCPN in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of the null plane and duration of geotropic DCPN in the head roll test are important findings for diagnosing persistent geotropic DCPN and determining its laterality [7,8]. Theories hold that the side of stronger nystagmus in the head roll test and side of the null plane must be the same, as has been reported in several studies [4,8,9]. In some cases of persistent geotropic DCPN, however, the stronger side in the head roll test and side of the null plane were opposite, which makes it difficult to determine the side of the affected semicircular canal, affecting treatment.…”
Section: Introductionmentioning
confidence: 67%
“…Persistent geotropic direction-changing positional nystagmus (DCPN) that differs from typical transient geotropic DCPN (canalolithiasis) has been proposed as a variant of horizontal semicircular canal-benign paroxysmal positional vertigo (HSCC-BPPV). In persistent geotropic DCPN, the specific gravity of the cupula is lower than that of the surrounding endolymph, which either activates or inhibits hair cells under the cupula according to the head position in the gravitational plane [1][2][3][4]. Possible mechanisms for persistent geotropic DCPN have been suggested, but its underlying pathogenesis is not known [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reliability of null point to determine the side of involvement is unclear. In a review of 27 patients with persistent positional nystagmus of the lateral canal, Seo et al. (2016) have reported that the affected side was determined on the same side as the neutral position in 18, on the opposite side in 4 and was not clear in the remaining 5 cases.…”
Section: Discussionmentioning
confidence: 99%